Compassionate care in radiography recruitment, education and training: A post-Francis Report review of the current literature and patient perspectives. Issue 3 (August 2016) - Bleiker, J.; Knapp, K.M.; Hopkins, S.; Johnston, G.
Abstract: Compassion is elemental in the care of a patient during their medical imaging (MI) procedure and is highly topical in the light of the Francis Report. The patient–practitioner interaction is an amalgam of context, communication and individual differences, and whilst compassion is a term in common parlance in the media, policy and radiographers' professional documents, its meaning and manifestation in radiography recruitment, education and practice are less clearly articulated. A review of the existing literature was undertaken, including a small scale study exploring patients' experiences in diagnostic medical imaging. Themes from the study included communication; competence; emotions; attitudes and relationships, but notably absent was any mention of compassion per se. Radiography research would benefit from further exploratory work into the nature of compassionate patient care in the unique context of the medical imaging encounter; offering an evidence-based contribution to radiography in the light of the Francis Report. Highlights: An increased focus on compassion was recommended in the Francis Report. Best compassionate care is a requirement in radiographers' Code of Professional Conduct. The meaning of compassionate patient care in radiography is not well understood. Equally neither is the expression of compassion in radiography. Research into compassion will contribute to evidence-based practice in radiography.